PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF DIGITALAUGMENTED REALITY 3D UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF ANAK DALAM PEMBELAJARAN DIFERENSIASI MATERI TATA SURYA - Dwi setiani; Yeri Sutopo; Agus Yuwono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the difficulties students face in understanding abstract and complex solar system material at the elementary school level. The purpose of this study was to develop interactive digital learning mediabasedon3D augmented reality (AR) to improve students' cognitive abilities through differentiated learning. The development model used was ADDIE, which consists of five stages: analysis, design, development, implementation, and evaluation. Data collection was conducted through expert validation, teacher and student questionnaires, and pretest and post test assessments to measure learning outcomes. Validation was performed by two media experts and three subjectmatter experts, followed by a pilot test with sixth-grade students at SD Negeri 1 Bandung. The research findings indicate that the developed 3D AR media falls in to the highly suitable category based on expert evaluations, is practical base don user feedback, and is effective in improving students' cognitive learning outcomes. These findings indicate that the integration of AR technology in differentiated learning can enhance student engagement, facilitate visual concept understanding, and support more meaningful learning at the elementary school level